Oil Sludge Ecotourism: Promoting Conservation in the North Coastal Area of Bintan Island - Akhmad, Dhanar Syahrizal; Kaloko, Ilhamda Fattah; Choirotunnisa, Maisaroh (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
The northern coast of Bintan Island, Indonesia, faces recurring oil sludge pollution during the northeast monsoon, primarily due to illegal discharges from ships in the Singapore Strait. This environmental threat has degraded coastal ecosystems, reduced fishery yields, and weakened tourism-based livelihoods. Currently, there is no coordinated response involving multiple stakeholders. Cleanup efforts are limited and fragmented. This study explores ecotourism as a strategic response to environmental and economic challenges. In response, the study introduces oil sludge ecotourism as a dual-purpose strategy that integrates coastal clean-up with sustainable tourism. By reframing remediation as a conservation-oriented experience, this model aligns with ecotourism principles emphasizing ecological restoration, community participation, and low-impact engagement with nature. It offers the potential to raise environmental awareness, diversify local incomes, and strengthen stewardship. If implemented effectively, oil sludge ecotourism could transform pollution-affected coastal zones into resilient, conservation-driven destinations. This model may serve as a replicable solution for other regions facing similar challenges, demonstrating how environmental degradation can be converted into opportunities for sustainable development.